Review on Impact of Chemical Fertilizers on Environment - Dr. Geeta Kandpal (International Journal of Modern Agriculture, 2021)
It is already known that for the quality production in agriculture, nutrition of plants is the most important aspect. Nutrient rates in soil affects the yield quality. In agricultural land, soil of the land in nutrients is poor, therefore, producers fertilize soil to increase the yield and quality. Many researches have shown extreme utilization of synthetic fertilizers for large scale plant production, however the consequence of which is environmental detioriation. Excess use of fertilizers can cause harmful effect on the environment. To reduce the adverse effect of the chemical fertilizers, organic fertilizers, bio fertilizers and Nano fertilizers have found to be more potent in increasing the productivity and with less or no side effects. The present review paper highlights the impacts of chemical fertilizers on the environment & use of alternatives of chemical fertilizers such as bio fertilizers, Nano fertilizers and slow released fertilizers to develop a healthy environment for present as well as future. In this review, objective to reveal the impact of the chemical fertilizer on the environment.